Should the dilated ascending aorta be repaired at the time of bicuspid aortic valve replacement?. (14th November 2017) - Kaneko, Tsuyoshi; Shekar, Prem; Ivkovic, Vladimir; Longford, Nicholas T; Huang, Chuan-Chin; Sigurdsson, Martin I; Neely, Robert C; Yammine, Maroun; Ejiofor, Julius I; Montiero Vieira, Vanessa; Shahram, Jasmine T; Habchi, Karam M; et al.
Abstract: OBJECTIVES: Bicuspid aortic valve (BAV) is the most common congenital valvular abnormality and frequently presents with accelerated calcific aortic valve disease, requiring aortic valve replacement (AVR) and thoracic aortic aneurysm and dissection. Supporting evidence for Association Guidelines of aortic dimensions for aortic resection is sparse. We sought to determine whether concurrent repair of dilated or aneurysmal aortic disease during AVR in patients with BAV substantially improves morbidity and mortality outcomes. METHODS: Mortality and reoperation outcomes of 1301 adults with BAV and dilated aorta undergoing AVR-only surgery were compared to patients undergoing AVR with aortic resection (AVR-AR) using Cox proportional hazards modelling and patient matching. RESULTS: Clinically important differences in patient characteristics, aortic valve function and aortic dimensions were identified between cohorts. Event rates were low, with rates of reoperation and death within 1 year of only 1.8% and 5.4%, respectively, and no aortic dissection observed during follow-up. There were no significant differences in reoperation or mortality outcomes between the AVR-only and AVR-AR cohorts. Age, aortic dimension or a combination thereof was not associated with better or worse outcomes after each AVR-AR compared with AVR. CONCLUSIONS: We conclude AVR-only and AVR-AR surgery have low morbidity and mortality and have utility over a wide range of age and aortic sizes. Our results do not provide support for the 45-mm aortic dimension recommended in the current guidelines for aortic resection while performing AVR or any other specific dimension.